PUBLIC SERVICE QUALITY : A Study on Learning Organization and Competency Apparatus Towards the Quality of Public Service at the National Agency for State Administration of the Republik of Indonesia - Mochtar, Sutarto.R (2010)
The decrease of public service quality at the Work Units of LAN RI is due to the lacks of contributions of learning organization implementation as well as the competency of apparatus. This has led the research to find out the influence of learning organization and apparatur competenccy towards the quality of public service with the management theory approach in the administrative sciences which covers organizational theory, leadership, and human resource management. The research method has been designed to be in the quantitative way with the descriptive and correlational forms with the use of regression analysis. The research results have shown that the learning organization and apparatus competency have strong influences towards the quality of public service with the value of R² = 0,843 atau 84,3%. Either learning organization or apparatus competency, each has a significant influence with the score of b1 = 0,567; b2 = 0,394 towards the quality of public service. The research findings are the decrease of public service quality at the Work Unit of LAN RI is due to the lacks of contributions of learning organization which are basically from the low level of personal mastery and mental models of apparatus. Also, the lacks of apparatus competency is due to the low level of knowledge, skills, and attitudes of employers. The recommendation for this research is that in order to enhance the quality of public service at the Work Units of the National Agency for State Administration, personal mastery as well as mental models should be taken into considerations so as to apply the learning organization concept. Moreover, the competency of employers can be increased with focusing on improving their knowledge, skills, and attitudes with the implementation of transformational leadership.